Identification of a conserved B-cell epitope on the GapC protein of Streptococcus dysgalactiae. (June 2015) - Zhang, Limeng; Zhou, Xue; Fan, Ziyao; Tang, Wei; Chen, Liang; Dai, Jian; Wei, Yuhua; Zhang, Jianxin; Yang, Xuan; Yang, Xijing; Liu, Daolong; Yu, Liquan; et al.
Abstract: Streptococcus dysgalactiae ( S. dysgalactia ) GapC is a highly conserved surface dehydrogenase among the streptococcus spp., which is responsible for inducing protective antibody immune responses in animals. However, the B-cell epitope of S. dysgalactia GapC have not been well characterized. In this study, a monoclonal antibody 1F2 (mAb1F2) against S. dysgalactiae GapC was generated by the hybridoma technique and used to screen a phage-displayed 12-mer random peptide library (Ph.D.-12) for mapping the linear B-cell epitope. The mAb1F2 recognized phages displaying peptides with the consensus motif TRINDLT. Amino acid sequence of the motif exactly matched 30 TRINDLT 36 of the S. dysgalactia GapC. Subsequently, site-directed mutagenic analysis further demonstrated that residues R31, I32, N33, D34 and L35 formed the core of 30 TRINDLT 36, and this core motif was the minimal determinant of the B-cell epitope recognized by the mAb1F2. The epitope 30 TRINDLT 36 showed high homology among different streptococcus species. Overall, our findings characterized a conserved B-cell epitope, which will be useful for the further study of epitope-based vaccines. Highlights: The mAb1F2 against Streptococcus dysgalactiae GapC was successfully generated. The motif 30 TRINDLT 36 is an epitope of the S. dysgalactiae GapC. Our findings are available for further study of epitope-based vaccines.